Al2O3–Al(OH)3-Based castable porous structures. Issue 6 (June 2015) - Souza, A.D.V.; Sousa, L.L.; Fernandes, L.; Cardoso, P.H.L.; Salomão, Rafael
Abstract Porous structures attained on the Al2O3–Al(OH)3 system present great technological appeal due to their high refractoriness, chemical resistance, compatibility with biological tissues and competitive costs. Due to these features, they can be used in many applications such as thermal insulation, hot gas filtration and catalyst support. This study presents a novel route to produce large parts of this kind of structure based on castable aqueous suspensions of calcined alumina (α-Al2O3), aluminum hydroxide (Al(OH)3) and hydratable alumina (ρ-Al2O3). After determination of the most favorable condition for dispersion, suspensions containing different proportions of calcined alumina, Al(OH)3 and hydratable alumina were cast and fired. Structures' sintering behavior was followed by dilatometry and porosity, pore size, mechanical strength, and elastic modulus measurements. Microstructure evolution was assessed using scanning electron microscopy. Varying the firing temperatures, several levels of total porosity were attained as well as a wide range of mechanical strength, rigidity and pore configuration.